Peran Orang Tua Dan Guru Dalam Penerapan Toilet Training Pada Siswa Autis Kelas VII di Sekolah Menengah Pertama Luar Biasa Negeri Branjangan Jember - Indah Roziah, Indah Roziah Cholilah; Fatihatul Mufidah, Fatihatul Mufidah (Sociocouns: Journal of Islamic Guidance and Counseling, 2024)
The application of toilet training to autistic children is different from normal children, because of the complex disorders children have difficulty implementing toilet training. Therefore, many parents of autistic children prefer practical things such as wearing diapers rather than training their children to defecate or urinate in the toilet. The focus of the problem studied in this thesis is: What is the role of parents and teachers in implementing toilet training for autistic children and what factors influence success and what obstacles are experienced. The aim of this research is to determine the role of parents and teachers in implementing toilet training for autistic children as well as the factors that influence success and the obstacles experienced. This research uses a descriptive qualitative approach, analyzing the role of parents and teachers in implementing toilet training for autistic students. The subjects in this research were autistic class teachers and parents of autistic students at the Branjangan Jember State Extraordinary Middle School. Data analysis uses data reduction, data presentation, and drawing conclusions. This research concluded: 1) The role of parents in implementing toilet training for autistic children is by providing an understanding of toilet training to children, providing encouragement by teaching toilet training regularly, providing examples during the toilet training implementation period, supervising children during the toilet training implementation period. . 2) The teacher's role in implementing toilet training for autistic students is by providing an understanding of toilet training by inviting students directly to the toilet, making a schedule of when students go to the toilet at school, providing examples of procedures for defecating or urinating ( BAK) in students. 3) factors that influence success in implementing toilet training for autistic students, namely the mother's level of knowledge about toilet training, the child's environmental factors, be it the family environment or school environment and family factors, the child's physical readiness, giving rewards to the child when they succeed in doing something 4) Obstacles What parents and teachers face in implementing toilet training for autistic students is children's difficulty in understanding toilet training, children who are not physically ready when toilet training is implemented.